Integrating Life Skills through Physical Activities Programs - A Anira; S Syarifatunnisa; Amung Ma'mun; Nur Indri Rahayu (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The purpose of this study was to investigate the integration of life skills through physical activities programs on the improvement of student life skills. The population of this study was 64 college students in Indonesia divided into two groups (experimental group n = 34 and control group n = 30). The sampling technique used cluster random sampling. The research method used was a quasi-experiment with a pre-test post-test control group design. The instrument used was the life skills scale for sport adaptation (LSSS) which consists of eight components, namely teamwork, goal setting, time management, emotional skills, communication, social skills, leadership, problem-solving, and decision making. The results showed that the physical activity integrated with the life skill program had a more significant impact on the improvement of the student's life skills than the physical activity without the integration of the life skill program. Further findings revealed that the social skill component was the life skill component that gained the highest increase. It shows that the integration of life skill programs in physical activities provides better results than physical activities without the integration of life skills programs.